SERTIFIKASI GURU; IDEOLOGI KAPITALISME DAN WELFARE STATE - Muh. Hanif (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2012)
Abstarct : The certification of Teachers is a government’s policy to assess teacher’s competencies in four areas as follows: professional, educational, social and personal competencies. Teachers who have passed the certification assessment will receive one multiple salary monthly. In the teacher certification policy, Indonesian government paying the salary of certified teachers is based on welfare state ideology. In this ideology, Indonesian government intervenes in fulfilling the fundamental rights of citizens, including education. By the certification of teachers program, Indonesian government tries to provide good education services to its citizens. The ideology of capitalism exists in the certified teacher attitudes who tend to be trapped in the culture of consumerism, by buying stuffs excessively which relatively has no relation to the improvement of teacher’s qualification. Key Words: The Certification of Teacher, Capitalism, and Welfare State